Transcatheter creation of a pulmonary artery to left atrial fenestration in a failing Fontan circulation using the Atrial Flow Regulator (AFR). (26th August 2021) - Pascall, Emma; Jones, Matthew I.; Savis, Alexandra; Rosenthal, Eric; Qureshi, Shakeel A.
Abstract: Transcatheter creation of an interatrial communication using the Occlutech Atrial Flow Regulator Device for pulmonary hypertension or heart failure is well described. We report a case of an 8-year-old boy with a failing Fontan circulation, in whom the Atrial Flow Regulator was used to successfully create a fenestration between the pulmonary artery and left atrium, improving his clinical condition.